Mechanical Characteristics of Coal Samples under Triaxial Unloading Pressure with Different Test Paths - Yang Zhang; Yongjie Yang; Depeng Ma (Shock and Vibration)
In order to understand the influence of unloading path on the mechanical properties of coal, triaxial unloading confining pressure tests with different initial confining pressure and different unloading rate were carried out. The test results show that the triaxial unloading strength of coal samples under different test conditions is lower than conventional triaxial tests, but the brittleness characteristics are more obvious. This result indicates that the coal samples are easily damaged under unloading conditions. In the axial loading stage of the confinement unloading tests, the axial strain plays a leading role. However, during the confining pressure unloading stage, the circumferential deformation is large, which is the main deformation in this stage. Higher unloading rates of confining pressure are associated with shorter times between the peak stress position and sample complete failure. This shows that samples are more easily destroyed under higher unloading rates and the samples are more difficultly destroyed under lower unloading rates. In addition, with increasing unloading rate, the peak principal stress difference and confining pressure at failure decrease gradually, whereas the confining pressure difference at failure increases gradually. Compared with conventional triaxial compression tests, the cohesion of coal is reduced and the internal friction angle is increased under the condition of triaxial unloading test.